Adding Handles to Optimize Manual Box Handling. (18th November 2018) - Nogueira, Helen Cristina; Januario, Leticia Bergamin; Moreira, Roberta de Fátima Carreira; Oliveira, Ana Beatriz
Abstract : The risk factors for developing musculoskeletal disorders in material handling tasks are well known. Among strategies for controlling risks, modifying boxes by adding handles is suggested. However, there are no clear recommendations regarding box modification as an approach to improve musculoskeletal health. In this study, we investigated the main literature databases to identify effects of box modification on reducing physical load. Electronic and manual searches were performed to identify studies that evaluated effects of boxes handles on physical exposure during handling tasks. The included studies were very heterogeneous (methods of assessment, types of handles used, and methodological quality), jeopardizing synthesis of evidence. Despite the mentioned limitations, we could suggest some features that could improve manual handling in practical settings, like the use of cylindrical handles forms with intermediate diameters (between 31 and 51 mm) and 30° inclination. Those characteristics demonstrated positive results on physical exposure. Regular cut-outs were indicated as a beneficial approach when boxes are handled in high surfaces. When handling occurs in medium heights or in the floor level, handles positioned on the top of the box might bring better results. Efforts to standardize methods are important to support both objective and subjective assessment of box handle design, as well to improve the internal validity of studies.